Effect of high-fat diets on oxidative stress, cellular inflammatory response and cognitive function - Tan, Bee Ling; Mohd Esa, Norhaizan (MDPI, 2019)
Cognitive dysfunction is linked to chronic low-grade inflammatory stress that contributes to cell-mediated immunity in creating an oxidative environment. Food is a vitally important energy source; it affects brain function and provides direct energy. Several studies have indicated that high-fat consumption causes overproduction of circulating free fatty acids and systemic inflammation. Immune cells, free fatty acids, and circulating cytokines reach the hypothalamus and initiate local inflammation through processes such as microglial proliferation. Therefore, the role of high-fat diet (HFD) in promoting oxidative stress and neurodegeneration is worthy of further discussion. Of particular interest in this article, we highlight the associations and molecular mechanisms of HFD in the modulation of inflammation and cognitive deficits. Taken together, a better understanding of the role of oxidative stress in cognitive impairment following HFD consumption would provide a useful approach for the prevention of cognitive dysfunction.